Modeling of rotary desiccant wheels - Harshe, Yogesh M.; Utikar, R. P.; Ranade, V. V.; Pahwa, D. (Chemical Engineering & Technology, 2005)
Rotary desiccant wheels are widely used in dehumidification and energy recovery applications. In this work, we have developed a 2D, steady state model of a rotary desiccant wheel. Mass and energy balance equations for the air streams and the desiccant wheels were developed. The hydraulic diameter and surface area for heat and mass transfer were calculated based on knowledge of the flute geometry. Appropriate correlations for the Sherwood number and Nusselt number were used to estimate heat and mass transfer coefficients. The model is capable of predicting steady state behavior of desiccant wheels having at the most three sections (process, purge, and regeneration). The mathematical model was validated using a real desiccant wheel, and the calculation results are in reasonable agreement with the experimental data. Based on this model, the temperature and humidity profiles in the wheel during both the dehumidification and the regeneration processes are analyzed. The simulated results were used to gain an insight into the operation of desiccant wheels. The model and the presented results will be useful for optimizing dehumidification and energy recovery applications.
Keywords: 1; 4-benzodioxan-2-carboxylate; 4-benzodioxan-2-carboxylic acid; doxazosin; enantio selectivity; enantiomeric ratio; ethyl 1; ethyl acetate; Lipases; transesterfication

Modeling of a fluidized bed propylene polymerization reactor operated in condensed mode - Utikar, Ranjeet P.; Harshe, Yogesh M.; Mehra, Anurag; Ranade, Vivek V. (Journal of Applied Polymer Science, 2008)
The gas-phase polymerization of propylene is one of the most widely accepted and commercially used processes for the manufacture of polypropylene (PP). Because of the highly exothermic nature of polymerization reactions, temperature runaway and subsequent polymer melting and agglomeration may occur, and the reactor has to be operated in a small operating window for safety. The addition of liquid monomer for heat removal (condensed mode) broadens the operating window and can substantially increase (by 50-100%) the capacity of given reactor hardware. This article describes the extension of a comprehensive mathematical model for the simulation of fluidized bed PP reactors to include the condensed mode of operations. The model is used to determine the influence of the operating parameters on the polymer properties and particle size distribution. The model is also used to determine the effects of two active sites and the reaction kinetics on macroscopic variables. The developed framework is useful for simulating multimonomer, multisite Ziegler-Natta-type olefin fluidized bed polymerization reactors operated under condensed mode. (C) 2008 Wiley Periodicals, Inc. J Appl Polym Sci 108: 2067-2076, 2008.
Keywords: Modeling; Polyolefins; Ziegler-Natta polymerization